Emulsion stabilization using ionic liquid [BMIM](+)[NTf(2)](-) and performance evaluation on the extraction of chromium - Goyal, R.K.; Jayakumar, N.S.; Hashim, M.A. (Elsevier, 2011)
This study focuses on the role of a hydrophobic ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [BMIM](+)[NTf(2)](-) in the preparation of emulsion liquid membrane (ELM) phase containing kerosene as solvent, Span 80 as surfactant, NaOH as internal phase and TOMAC (tri-n-octylmethylammonium chloride) a second ionic liquid as carrier. The first time used [BMIM](+)[NTf(2)](-) in ELM was found to play the role of a stabilizer. The emulsion prepared using [BMIM](+) [NTf(2)](-) has a long period of stability of about 7h (at 3% (w/w) of [BMIM](+)[NTf(2)](-)) which otherwise has a brief stability up to only 7min. The stability of the emulsion increases with the increase in concentration of [BMIM](+)[NTf(2)](-) up to 3% (w/w). Nevertheless, with further increase in concentration of [BMIM](+)[NTf(2)](-), a reduction in the stability occurs. The extraction experiments were carried out after holding the ELM for 2h after the preparation and a removal efficiency of approximately 80% was obtained for Cr. The destabilization of the emulsion was studied by observing the change in the interface height. An empirical correlation for the stability of the emulsion has been proposed.